Neuronal Differentiation in a Pituitary Macroadenoma with Focal Small Blue Round Cell Morphology: Report of a Rare Pattern - Hisham Alkhalidi (Hindawi Limited, 2020)
Ganglion cell-containing pituitary adenomas that are neurofilament protein-positive are the exceedingly rare form of pituitary ganliocytomas. We report a case of a 23-year-old male patient who presented with a clinical picture of acromegaly in addition to raised prolactin level. Histopathology showed areas exhibiting pseudopapillary and solid proliferation of round and monotonous blue cells. The immunohistochemistry showed strong reactivity for synaptophysin and growth hormone and focal reactivity to prolactin. Fibrous bodies are confirmed using cytokeratin immunostain, in keeping with sparsely granulated somatotroph component. The patient remained free of recurrence after one year of radiological follow-up.